Clinical Features of Patients with Episcleritis and Scleritis in an Italian Tertiary Care Referral Center. Issue 3 (May 2014) - Berchicci, Luigi; Miserocchi, Elisabetta; Di Nicola, Maura; La Spina, Carlo; Bandello, Francesco; Modorati, Giulio
Purpose: To evaluate demographic characteristics, clinical features, systemic disease associations, visual outcomes, and treatment modalities of patients with episcleritis and scleritis in an Italian tertiary care referral center. Methods: Data from 25 patients with episcleritis and from 85 patients with scleritis followed from 2003 to 2012 were retrospectively evaluated. The main outcome measures were demographics, ocular disease characteristics, presence of systemic associated disease, treatment regimen, and follow-up period. Results: Episcleritis and scleritis were found bilaterally in 24% and 31% of patients, respectively (p<0.521). The episcleritis was diffuse in 15 and focal in 10 patients, while the scleritis was diffuse in 49, nodular in 28, necrotizing in 6, and posterior in 2 patients. Anterior uveitis (4% vs 31%; p<0.006), peripheral ulcerative keratitis (0% vs 14%; p<0.167), ocular hypertension (0% vs 7%; p<0.333), and a decrease in visual acuity (4% vs 19%; p<0.112) were encountered as ocular complications in patients with episcleritis and patients with scleritis, respectively. An associated systemic disease was found in 20% and 52% of patients with episcleritis and patients with scleritis (p<0.004). Among patients with episcleritis, 76% required topical corticosteroid treatment to achieve disease resolution, 16% oral nonsteroidal anti-inflammatory drugs (NSAIDs), and 8% antivirals; 39% of patients with scleritis required systemic NSAIDs, 12% oral corticosteroids, 34% immunosuppressive drugs, and 15% antibiotics or antivirals. Conclusions: The importance of differentiating scleritis from episcleritis is remarkable given the significant difference in the degree of ocular complications and associated systemic diseases between these ocular conditions. Prompt diagnosis, systemic assessment, and treatment are fundamental in all patients with scleral inflammation.